2021
DOI: 10.3390/antiox10081326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Nanoencapsulated Moringa Leaf Ethanolic Extract on the Physiology, Metabolism and Reproductive Performance of Rabbit Does during Summer

Abstract: This study investigated the effect of Moringa leaf ethanolic extract (MLEE) on heat-tolerance variables and the reproductive performance of rabbit does bred under hot climate conditions. Additionally, the effect of nanoencapsulation technology on the biological efficiency of MLEE was considered. A total of 56 rabbit does were randomly divided into four experimental groups and treated with 50 mg/kg body weight (BW) nonencapsulated MLEE, 25 or 10 mg/kg BW nanoencapsulated MLEE, or not treated (Control, C). The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…These results are similar to those observed in litter weight at 21 days by Marai et al ( 6 ) and at 35 days by Marai et al ( 35 ). The amelioration of these parameters, following the administration of Moringa oleifera aqueous seed extract in this study, has also been demonstrated by El-Desoky et al ( 52 ) in female rabbits receiving, respectively, 10, 25, and 50 mg/kg body weight of nonencapsulated Moringa oleifera leaves ethanolic extract during summer seasons. Moreover, various phenol compounds and vitamin C found in Moringa oleifera have the ability to prevent the digestive system cell membranes from oxidative stress by scavenging O 2 radicals and, therefore, restoring feed utilization ( 53 ).…”
Section: Discussionsupporting
confidence: 86%
“…These results are similar to those observed in litter weight at 21 days by Marai et al ( 6 ) and at 35 days by Marai et al ( 35 ). The amelioration of these parameters, following the administration of Moringa oleifera aqueous seed extract in this study, has also been demonstrated by El-Desoky et al ( 52 ) in female rabbits receiving, respectively, 10, 25, and 50 mg/kg body weight of nonencapsulated Moringa oleifera leaves ethanolic extract during summer seasons. Moreover, various phenol compounds and vitamin C found in Moringa oleifera have the ability to prevent the digestive system cell membranes from oxidative stress by scavenging O 2 radicals and, therefore, restoring feed utilization ( 53 ).…”
Section: Discussionsupporting
confidence: 86%
“…Al-Sagheer et al ( 112 ) suggested that addition of 1,000 mg·kg −1 in diet could improve the hematological and antioxidative indicators, and efficiently mitigate the detrimental effects of chronic temperature stress on performance, hematobiochemical features, and oxidative stability. El-Desoky et al ( 113 ) indicated that nanoencapsulated MLEE has 30 active components, which alleviates (supplemental dose of 10 mg·kg −1 body weight) the negative impacts of heat stress by improving metabolism, redox status, and hormonal balance of rabbit does during summer, thereby increase the reproductive performance (e.g., total litter size, kindling rate, litter size at birth and litter weight at birth). The mode of action of plant extract is complex due to it contains a variety of active components, which still needs further in-depth researches.…”
Section: Potential Mitigation Strategies Of Nutritional Interventionmentioning
confidence: 99%
“…For example, heptadecane, epi-bicyclosesquiphellandrene, delta-Cadinene naphthalene, ethofumesate, 2-ethylacridine, 4H-pyrane-3-carboxamide, ethidimuron, and hexadecanoic acid are some plants metabolites with antibacterial, anticancer, pesticide, herbicide, and antioxidant e cacy which were produced by BR6 (Table 4). These results can con rm the remarkable similarity between the endophytic fungi and P. bracteatum in terms of producing secondary metabolites [33][34][35][36][37] .…”
Section: Screening Of Fungal Extracts For Morphinan Alkaloidsmentioning
confidence: 54%